Agricultural Engineering Vocational School in Aceh Besar with Behavior Architecture Approach - Amiria, Musawir; Fuady, Zahrul (Rumoh Journal of Architecture, 2024)
Currently, Aceh Besar District has a PP Negeri Saree Vocational School in the agricultural section in Saree Aceh Besar, but this school only studies agricultural information. The condition of Aceh Besar District shows that their land use majority is used for agriculture, animal farming and husbandry, fisheries and paddy fields, farm, and other plantations. Abundant natural resources are not processed into a good business due to a shortage of human resources in the field of agricultural engineering. Therefore, it is necessary to include an Agricultural Engineering in those vocational school with aims to create human resources in the field of agricultural machinery and agribusiness. The object design location is on SIM Airport Street, Gani, Kec. Want Jaya, Aceh Besar. The classification of the Agricultural Engineering Vocational School includes the Department of Agricultural Engineering and Agricultural Product Processing Agribusiness. The approach of behavior architecture into the design is behavior setting in completing spatial design, spatial cognition in completing circulation, and environment perception in completing image or building appearance. The analysis used is functional analysis, site analysis and user analysis. The Agricultural Engineering Vocational School in Aceh Besar is designed on an area of 14,950 m2 with multiple building masses. The ground coverage area (KDB) is 40% which is 5,980 m². The facilities in the building meant to support students in the learning process and as well as supporting facilities, those facilities are practice rooms, namely rice threshing machine engineering rooms, rice processing , rice polisher machine, hand tractor, technology for processing agricultural products, quality testing and quality control practice room.